Pressure-Driven Batch Distillation Optimal Control for Acetone-Methanol Separation - Stojkovic, Marija (Fine Chemical Engineering, 2024)
Over the last fifteen years, immense progress has been made in the research of pressure-swing batch distillation. The challenge lies in the fact that certain pressure-sensitive azeotropic mixtures cannot be separated in a regular open batch mode with an acceptable outcome. Throughout most of this text, findings contradict previously established facts. The separation of acetone-methanol by pressure-swing batch distillation in a mixed double system, consisting of a regular and inverted column, is the process under investigation. In this work, a comprehensive global solution to the optimal control problem is derived in the form of a sequential synthesis of controlled trajectories. A thorough analysis of the control variables, with and without parametric sensitivity of manipulated variables, on the optimal control pattern with variable reflux is presented. Most authors did not achieve significant results by simultaneously optimizing reflux and liquid division ratios or by using a "variable pressure gap." This study challenges previous findings, emphasizing the importance of simultaneous optimization of all three factors mentioned. During this study, the optimal reflux strategy through cyclic operation was extended to optimize energy expenditure over a fixed time horizon. Moreover, the proposed scheme offers a high level of operational flexibility, allowing units to be operated independently or as a system. Additionally, the facility of connecting additional devices is highlighted by the significant difference in output temperatures and the potential for using evaporated fluids consecutively. Lastly, the research provides a solid basis for future investigations into internal and external heat integration, potentially leading to conclusions about expanding the network using well-known heat cycles.